Theoretical and Practical Aspects of Psychological and Pedagogical Support for Children and Adolescents Temporarily Displaced from the Territories of Permanent Residence - Popova, Olga; Koval, Liudmyla; Horetska, Olena; Serdiuk, Nataliia; Burnazova, Vera (Journal of History Culture and Art Research, 2018)
Many children and adolescents experience traumatizing occurs including but not limited to military attacks, death of close people, demolition of houses, witness to the death of others, refugee status etc. These people need help and support of specialists to restore their psycho-emotional state, to overcome the consequences of post-traumatic stress disorder. This need increases the role of educational institutions, namely the professional activity of teachers and practical psychologists, which require improvement of existing and development of new methods of social adaptation and psychological and pedagogical rehabilitation of children and adolescents temporarily displaced from the ATO zone (Anti-Terrorist Operation Zone) in Ukraine to overcome symptoms of post-traumatic stress disorder. Teachers and students of the Berdiansk State Pedagogical University actively participate to develop pedagogical assistance and support for children and adolescents, who temporarily displaced from the territory of the ATO zone, to overcome the consequences of traumatic events and solve their own psychological problems. By elaborating this experience, this study concludes that the optimal development of the child occurs in a family where each member has influence on him; the restoration of the state of mind is possible if the qualified psychological and pedagogical support will be organized; overcoming of psychotrauma will be effective when social contacts with other people will be established. The close cooperation of psychologists and teachers with parents, the educational environment will speed up the process of rehabilitation and adaptation of children and adolescents who are experiencing post-traumatic stress disorder.